Comportamiento meiótico de diferentes especies de lulo, Solanum sp (2010)
An analysis of meiotic behavior of lulo species S. hirtum, S. quitoense and S. sessiliflorum, following the conventional methodology for studies of microsporogenesis was realized. Flower buds were taken at different stages of development, fixing them for 24 hours in a solution of three parts of ethanol per one part of acetic acid, saturated with traces of ferric chloride crystals. For the preparation of the slides following the technique of squash, releasing pollen mother cells and finally made the observations under light microscopy. The analysis showed that meiosis occurs in anther ranging from 2.79 to 4.45 mm. Meiotic normality was 100% for both meiosis I and II. The meiotic index in all three species was 99,98% indicating that they are good parental for use in crossbreeding programs. The three species have the same number of chromosomes (2n = 2x = 24). The frequency of abnormalities during the meiotic process was lower for S. hirtum, and high for S. quitoense, however, the pollen viability was of great magnitude (91.2-97.3%).